Unprotected Sex among Sexually Active Unmarried Young Adults: A Pariah or Preemptive Incidence - Bankole, Taofik Olatunji; Yinusa, Rasheed Adebayo; Shamaki, Muazu Alhaji (Journal of Diseases, 2019)
Globally, HIV endemic has been linked to several but preventable predictors, amongst these, is the practice of unprotected sex. In spite of the burdens of HIV/AIDS in Nigeria, there is a dearth of studies with focus outside the conventional approach to predicting the incidence of unprotected sex among sexually active unmarried young adults in Nigeria. This study addresses this limitation. The study adopted a cross-sectional and multistage sampling technique. A total sample size of 384 respondents was systematically and randomly selected among young adults aged 20-29 in Ile-Ife, Osun State, Nigeria. Unprotected sex was the study’s response variable and was categorised into respondents who had unprotected sex in at least the last three months prior the survey with single sex partner and those who had with multiple sex partners over the same period. The key explanatory variables were a pariah and preemptive factors while the confounding variable was knowledge of HIV/AIDS. Rank-ordered logistic regression was employed using Stata 14. Results showed that pariah and preemptive factors were significantly associated with unprotected sex (p<0.05). The study concluded that the incidence of unprotected sex among unmarried young adults across Ile-Ife communities was predisposed to pariah and preemptive factors.